El Código del Trabajo y la determinación de las reglas claras para la transacción en materia laboral. - VALDIVIESO JARAMILLO, FRANCISCO JAVIER (2013)
The subject-matter of this thesis has great significance in the social, economic and labor, and is directly related to the subject transaction. The transaction usually takes place when, arrival termination of the contract, the worker accepts as payment of a sum less employment benefits to which law applies, so by the economic situation to be faced with being unemployed. The work is scheduled transaction in the Constitution of the Republic, however this applies provided that no waiver means and shall be held before a competent court or administrative authority, but the Labour Code does not provide the relevant rules to implement this provision constitutional, so this legal institution of the transaction can be misused and that is misused, the pretext of resolving the dispute. From a legal perspective, the present research related to labor law has significance, because it allows to determine the negative consequences caused by the lack of determination of the procedure to be followed in the event that the litigants decide to pursue a transaction work. The legal problem has posed a serious social impact, because within the processes of the Labor Law is not being guaranteed the right to legal certainty and cannot make the principle pro worker. Furthermore, the impact of work involves a judgment, it is the duty of the state to ensure that the provisions of the Constitution, so that the transaction cannot be misused,hence as demonstrated in this thesis legal, it is urgent to reform the Labour Code.